Unravelling provenance from Eocene-Oligocene sandstones of the Thrace Basin, North-east Greece - Caracciolo, Luca; et al. (Sedimentology, 2011)
New sandstone petrology and petrostratigraphy provide insights on Palaeogene (Middle Eocene to Oligocene) clastics of the Thrace Basin in Greece, which developed synchronously with post-Cretaceous collision and subsequent Tertiary extension. Sandstone petrofacies are used as a tool to unravel complex geodynamic changes that occurred at the southern continental margin of the European plate, identifying detrital signals of the accretionary processes of the Rhodope orogen, as well as subsequent partitioning related to extension of the Rhodope area, followed by Oligocene to present Aegean extension and wide magmatic activity starting during the Early Oligocene. Sandstone detrital modes include three distinctive petrofacies: quartzolithic, quartzofeldspathic and feldspatholithic. Major contributions are from metamorphic basement units, represented mostly by low to medium-grade lithic fragments for the quartzolithic petrofacies and high-grade metamorphic rock fragments for the quartzofeldspathic petrofacies. Volcaniclastic sandstones were derived from different volcanic areas, with a composition varying from dominantly silicic to subordinate intermediate products (mainly rhyolitic glass, spherulites and felsitic lithics). Evolution of detrital modes documents contributions from three key source areas corresponding to the two main crystalline tectonic units: (i) the Variegated Complex (ultramafic complex), in the initial stage of accretion (quartzolithic petrofacies); (ii) the Gneiss-Migmatite Complex (quartzofeldspathic petrofacies); and (iii) the Circum-Rhodope Belt. The volcaniclastic petrofacies is interbedded with quartzofeldspathic petrofacies, reflecting superposition of active volcanic activity on regional erosion. The three key petrofacies reflect complex provenance from different tectonic settings, from collisional orogenic terranes to local basement uplift and volcanic activity. The composition and stratigraphic relations of sandstones derived from erosion of the Rhodope orogenic belt and superposed magmatism after the extensional phase in northern Greece provide constraints for palaeogeographic and palaeotectonic models of the Eocene to Oligocene western portions of the Thrace Basin. Clastic detritus in the following sedimentary assemblages was derived mainly from provenance terranes of the Palaeozoic section within the strongly deformed Rhodope Massif of northern Greece and south-east Bulgaria, from the epimetamorphic units of the Circum-Rhodope Belt and from superposed Late Eocene to Early Oligocene magmatism related to orogenic collapse of the Rhodope orogen. The sedimentary provenance of the Rhodope Palaeogene sandstones documents the changing nature of this orogenic belt through time, and may contribute to a general understanding of similar geodynamic settings.
Keywords: Eocene-Oligocene; magmatism; North-east Greece; Rhodope Massif; sandstone detrital modes; Thrace Basin